Nose-to Brain Delivery of Resveratrol, a Non-Invasive Method for the Treatment of Cerebral Ischemia - Iván Alquisiras-Burgos; Irma Gabriela González-Herrera; Sergio Alcalá-Alcalá; Penélope Aguilera (MDPI AG, 2024)
Cerebral ischemia represents a particular condition among neurological diseases due to its high frequency, high associated mortality, and the permanent disability in patients that survive it. Numerous studies in animal models have demonstrated the protective properties of resveratrol against cerebral ischemia. Resveratrol is a soluble molecule in polar solvents with high membrane permeability; however, it is rapidly metabolized at the liver and is also a substrate of the ATP binding cassette transporters located at the blood-brain barrier. These circumstances reduced bioavailability of resveratrol to the brain. In this review, we examined nasal resveratrol's formulations including nanocarriers such as nanostructured lipid carriers, nanoemulsions, nanoparticles, bilosomes, cubosomal, and transferosomes that are directly transported to the brain. An intranasal administration route evades resveratrol transformation due to liver metabolism. Components of nanoformulations increased resveratrol absorption to the brain by enhancing permeation through specific approaches and also maintaining stability during storage. Both characteristics improved the delivery of resveratrol with conserved antioxidant capacity and protective properties for neurological models. Although demonstration that the nanoformulations prevents resveratrol's blood-brain barrier retention is missing, properties of resveratrol's nanoformulation encourage testing in clinical trials; however, regulatory approval for a novel nanocarrier in nasal drug delivery is complicated and needs approval.